“Métodos de introducción de cenldas reales para la formacion de nucleos de abejas Apis mellífera L., en colmenar del caserío de aucaloma – Lamas” - Cueva Del Castillo, Víctor Armando (2007)
The present work took effect in hives prevailed located in Aucaloma's group of houses. Sector Bijao, under half way environmental conditions controlled in the November period of the 2006 to April of the 2007, for the sake of evaluating bees's different nuclei formados by means of two methods of introduction of real cells. The experimental units utilized in the essays nuclei with capability in order to 5 Mark corresponded to equipped nuclei in porthole. bees's nuclei were colognes obtenidos mothers, previously equipped to this end, them as evaluados went with Mann's test - Withney with 8 repetitions in order to each treatment. tried treatments attended : real- cells introduction without protector (au naturel) and for introduction of real cells with protector West, consisting each repetition in nucleus of bees contained in a portal beehive nucleus, once was fixed for five honeycombs, two reservedly nutritious, two with offspring operculada of workwoman and the remainder contained the real cells in number made suitable. Pre's register of the start of the posture or period Took effect - oviposition, 1 number of eggs to the 7, 15 and 30 days after initiate posture .. larvas's number to initiate's 7, 15 and 30 days the posture, cold sores number (opérculos) to them 7, 15 and initiate's 30 days the posture and adults's relative quantity, coming true the statistical analysis for each one of these aspects evaluados. The aftermaths they permitted obtenidos establishing than the days to the posture's start or Pre's period - oviposition in arder to the treatment fer introduction of real cells without protector (native) on the average became of 11. 75 days, while he stops the treatment for introduction of cells grate (subj) average became of 14.25 days with protector. The number of eggs, to the 7 days after initiate the posture in arder to the treatment for introduction of real cells without protector ( native) hada 7.89- eggs average for 9 cm2 af haneycomb, while the treatment far intraductian af real cells with protector staps average he went from 10.17 eggs. This characteristic evaluated 15 days after initiate the posture 1 search in arder to the treatment for introduction of real cells without protector (au naturel) a 2.51- eggs average for 9 cm2 of honeycomb and in order to the treatment for introduction of real cells with protector 2.55- eggs West. 30 days after initiate the posture in arder to this same characteristic, the treatment for introduction of real cells without protector 1 search a 6.08- eggs average for 9 cm2 of honeycomb, while West stops the treatment for introduction of had jealousy reales with protector 1 register an average of of 6.04. 1 number of larvas In order to the characteristic, 7 days after initiate the posture, in order to the treatment for introduction of real cells without protector (au naturel) search him an average 14.97 larvas for 9 cm2 of honeycomb and in order to the treatment for introduction of real cells with protector West went from 11.27 larvas. This characteristic, 15 days after initiate the posture 1 search 3.38 larvas's average far 9 cm2 of honeycomb in arder to the treatment for introductian of real cells they are protector ( au naturel) and of 4.99 larvas in arder to the treatment for introduction of real cells with protector West.. 30 days after initiate the posture in arder to this same characteristic in arder to the treatment for introduction of real cells natural average went from 6.50 larvas for 9 cm2 of honeycomb, while West stops the treatment for introduction of real cells with protector he went from 8.54 larvas. In order to the cold sores (opérculos), 7- days number after initiate_the_posture in order to the treatment for introduction of real cells without protector (natural) search him a 0.32- cold sores average (opérculos) for 9 cm2 of honeycomb and in order to the treatment for introduction of real cells with protector West went from 0.39 cold sores (opérculos). This same characteristic evaluated 15 days after initiate the posture 1 search a 14.13- cold sores average (opérculos) for 9 cm2 of honeycomb and in order to the treatment for introduction of real cells with protector West obtained a 13.02- cold sores average (opérculos). 30 days after initiate the posture the posture averages were, in order to the treatment for introduction of real cells without protector (au naturel) 5.68- cold sores fu (opérculos) for 9 cm2 of honeycomb. And of 8.14 cold sore (opérculos) in order to the treatment for introduction of real cells with protector. The relative quantity of adults, record maximum moral values and minimums in order to each treatment. In order to the treatment for introduction of real cells without protector (au naturel) the mínimum 3 of the scale that is equivalent corresponded to number to middling population and the higher scale 1 search the number 5 that is equivalent to very high population, while West stops the treatment for introduction of real cells with protector the mínimum 1 catch up with the number 3 in the scale that corresponds to mediate population and the peak to the number 5 that corresponds to very high population. In general, both methods, they demonstrated being viable and with a similar behavior in the different stages of the metamorphosis of the castes in order to the newcolognes formation.